The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1985
DOI: 10.1080/10862968509547535
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Repeated Readings and Attentional Cues on Reading Fluency and Comprehension

Abstract: The failure of some researchers to find improved reading comprehension with increased fluency may result from the assumption that readers automatically shift attention to comprehension when fluency is established. Research on cuing readers to a purpose in reading suggests that a simple cue about comprehension may be sufficient to prompt this attentional shift. In this study, the effects of repeated readings and attentional cues on measures of reading fluency and comprehension were examined. Thirty third grader… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
93
0
2

Year Published

1995
1995
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(106 citation statements)
references
References 12 publications
11
93
0
2
Order By: Relevance
“…They found that fluency was greatest when the new passage contained overlapping words and there were no fluency effects when the words in the passage were not overlapping (Rashotte & Torgesen, 1985). Both of these studies show the effectiveness of repeated reading in improving reading fluency of this text (O'Shea et al, 1987;Rashotte & Torgesen, 1985).…”
Section: Existing Interventions For Reading Fluencymentioning
confidence: 76%
See 1 more Smart Citation
“…They found that fluency was greatest when the new passage contained overlapping words and there were no fluency effects when the words in the passage were not overlapping (Rashotte & Torgesen, 1985). Both of these studies show the effectiveness of repeated reading in improving reading fluency of this text (O'Shea et al, 1987;Rashotte & Torgesen, 1985).…”
Section: Existing Interventions For Reading Fluencymentioning
confidence: 76%
“…O'Shea, Sindelar and O'Shea (1987) found that students who re-read the same text seven times read at a greater fluency rate than those who only read the passage once, twice or three times. Rashotte and Torgesen (1985) state that for repeated reading to be effective in improving reading fluency over a seven day period each passage must be read four times before the child is presented with the next passage.…”
Section: Existing Interventions For Reading Fluencymentioning
confidence: 99%
“…However, the majority of the early studies found repeat reading the same text to fluency helped children improve decoding, and ultimately children's reading comprehension of the specific text repeatedly read [48]- [54]. One study showed an increase in reading comprehension when students were asked to pay attention to what they were reading [53].…”
Section: The Repeat Reading Studiesmentioning
confidence: 99%
“…According to Logan, each time a reader attends to text, an instance or trace of that text is automatically encoded in memory at the sublexical, lexical, phrase, and text levels. As these instances build up-within a relatively few repetitions (three to five according to many authors; e.g., O'Shea, Sindelar, & O'Shea, 1985, 1987Reutzel, 2003)-they become relatively easier to retrieve (following the power law of learning; Logan, 1997). As a result, a given instance becomes readily available for retrieval at a later point.…”
Section: Instance Theory Of Automaticitymentioning
confidence: 99%